Analysis of thermo-mechanical coupling of high-speed angular-contact ball bearings. (June 2017) - Ye, Zhenhuan; Wang, Liqin; Chen, Guanci; Tang, Di
In view of the thermo-mechanical coupling effect that commonly exists in the loading zone of angular-contact ball bearings while the bearings are operated, several process parameters are analyzed, including coordination condition of thermal expansion–deformation load, interaction relationship of contact stress, friction heat, and temperature raised in the loading zone of bearings. Based on the dynamic method of rolling bearings and finite element analysis method, the thermo-mechanical coupling calculation model of angular-contact ball bearings is established and solved. Based on the model, the influences of coupling effect on temperature field, loading characteristics, and fatigue life of bearings are analyzed. Then, the influence of geometric parameters and working conditions of bearings on the thermo-mechanical coupling effect are discussed. The results show that there are differences in the results of temperature distribution, loading characteristics, and fatigue life while the thermo-mechanical coupling effect is considered or not in the bearings analysis; furthermore, the mentioned differences vary with the different geometric parameters and working conditions.